Narrative of Jesus’ Social Interactions in the Gospel of Luke as a Relational Foundation for an Inclusive Church - Kakunsi, Orlando Yos; Mawikere, Marde Christian Stenly; Marpaung, Agus Marulitua (Peneliti.net, 2025)
Pluralistic Indonesia often encounters challenges in cultivating harmonious social interaction. This article examines the narrative of Jesus Christ’s social interaction in the Gospel of Luke as a theological foundation for an inclusive and participatory Church. Employing a qualitative-descriptive method through literature study, the research explores how Jesus established relationships that transcended social, cultural, and religious boundaries. The focus is placed on His actions, values, and social responses toward various groups—including those marginalised. The findings reveal that Jesus’ social interactions embody divine hospitality and present a transformative relational model. The contemporary Church is thus called to reflect upon and embody these values within a pluralistic social context. This study affirms the relevance of Lukan theology in shaping a Church fellowship that responds to social challenges with inclusivity and dialogue.